The influence of fitness celebrity livestream on women’s exercise behavior intention: a moderated mediation model - He, Jianfeng; Yao, Zijun; Shangguan, Yuwen; Li, Huan (Frontiers in Psychology, 2025)
ObjectiveUtilizing the S-O-R model as a guide, this research delved into how celebrity characteristics and media content characteristics impact women’s behavioral intentions. The study zeroed in on the role of body satisfaction as a moderator in the relationship between social presence and women’s exercise behavioral intentions. The aim is to reveal the intrinsic mechanism of the influence of fitness stars’ live streaming on women’s exercise behavior intention and to provide theoretical support to enhance women’s exercise intention, improve physical health, and help the implementation of the national health strategy. This study provides important theoretical support for the implementation of the national health strategy.MethodsA cross-sectional questionnaire survey was administered to a convenience sample of 382 female participants. Data analysis was performed using SPSS and AMOS; reliability analysis was first conducted to assess measurement consistency, followed by confirmatory factor analysis to validate the measurement model. Common method bias was then assessed using Harman’s single-factor test. Finally, both regression analysis and structural equation modeling were employed to test the hypothesized relationships in the theoretical framework.ResultsSocial presence mediated the relationship between celebrity characteristics: expertise (β = 0.207, p < 0.001), trustworthiness, (β = 0.195, p < 0.001) attractiveness (β = 0.251, p < 0.001), media content characteristics: perceived usefulness (β = 0.253, p < 0.001), perceived ease of uses (β = 0.224, p < 0.001) and women’s exercise behavior intentions. Body satisfaction moderated the relationship between social presence and women’s exercise behavior intentions.ConclusionThis study provides key theoretical and practical contributions by validating social presence as a mediator and body satisfaction as a moderator in the relationship between live-streaming stimuli and women’s behavioral intentions.